Miejsce i rola mediów lokalnych we współczesnym społeczeństwie informacyjnym (refleksje medioznawcze) - Kowalczyk, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
The author deals with the issue of the positioning of local media in a local information system. He considers this issue from the perspective of media studies and refers to the results of surveys carried out over the past twenty years, that is after 1989. The paper intends to present selected areas of the analysis of local media as an important participant in dialogue and a forum for the exchange of arguments in a local information system. The author emphasizes the social and political consequences of two fundamental paradigms of the functioning of local media, namely freedom of speech and accountability for one’s words, which are considered not only in terms of the execution of the right to access information, but also in terms of the social responsibility of the media for the information they disseminate.